The impact of digital technology application and digital capabilities in enhancing the digital export performance of Vietnamese enterprises - Nguyen Hoang Quy; Nguyen Thi Phuong Lan (Journal of State Management, 2024)
This paper analyzes the role of digital technology and digital capabilities in enhancing the digital export performance of Vietnamese enterprises. Quantitative research on 266 enterprises reveals that applying digital technology and developing digital capabilities significantly enhances export efficiency. Notably, the synergy between these two factors creates a more robust and positive impact on digital export performance. Based on these findings, the paper offers practical recommendations for exporting enterprises and policy suggestions for the Government and state agencies to facilitate digital export activities in Vietnam within the context of globalization.